1996
DOI: 10.1046/j.1365-2249.1996.d01-618.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma (IFN-γ) treatment decreases the inflammatory response in chronic Pseudomonas aeruginosa pneumonia in rats

Abstract: SUMMARYIn a rat model of chronic Pseudomonas aeruginosa lung infection mimicking cystic fibrosis (CF), we studied whether the inflammatory response could be altered by intraperitoneal treatment with recombinant rat interferon-gamma (rrIFN-). Rats were treated either before or after intratracheal challenge with P. aeruginosa embedded in alginate beads. Rats treated after challenge had a significant reduction in the severity of macroscopic lung inflammation compared with rats treated before challenge (P 0 : 004)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 35 publications
2
48
1
2
Order By: Relevance
“…It is reported in one study that the association between cytokine-producing frequencies in αβ and γδT cells are as follows: TNF-α >IFN-γ >IL-2 (33). The beneficial role of the inflammatory cytokine IFN-γ has been confirmed by previous studies (34), and a lower IFN-γ secretion from T cells is found in patients with cystic fibrosis (35). Additionally, IFN-γ and TNF-α are reported to show suppressive effects on white blood cell precursors (36).…”
supporting
confidence: 55%
“…It is reported in one study that the association between cytokine-producing frequencies in αβ and γδT cells are as follows: TNF-α >IFN-γ >IL-2 (33). The beneficial role of the inflammatory cytokine IFN-γ has been confirmed by previous studies (34), and a lower IFN-γ secretion from T cells is found in patients with cystic fibrosis (35). Additionally, IFN-γ and TNF-α are reported to show suppressive effects on white blood cell precursors (36).…”
supporting
confidence: 55%
“…Therefore, in the absence of IRF-1, P. aeruginosa-induced inflammation develops in the context of reduced Th1 responses. Because Th1 cytokines seem to favor clearance of P. aeruginosa (16,29), the low levels of IRF-1 present in CF patients' epithelia (18) might contribute to the persistence of P. aeruginosa infection and the chronic inflammation of the CF patient lung. …”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34] The histopathologic features of rats 35 and mice 36 inoculated with P. aeruginosaladen agarose beads closely mimics that of CF patients, which includes endobronchitis, bronchopneumonia, bronchiectasis, mucus plugging and alveolar exudates with acute and chronic inflammatory cells. The inoculation of sterile agarose beads is associated with minimal inflammation, 36 however, as confirmed in the current study.…”
Section: Discussionmentioning
confidence: 99%